1986
DOI: 10.1088/0022-3727/19/4/021
|View full text |Cite
|
Sign up to set email alerts
|

Hot electron emission from composite metal-insulator micropoint cathodes

Abstract: Field electron emission measurements have been made on composite emitters consisting of electrolytically etched tungsten micropoint cathodes overlayed by a 40-200 nm thick layer of epoxy resin. Their emission properties include (a) an initial switch-on effect at threshold fields of approximately 109 V m-1, (b) a subsequent reversible I-V characteristic that gives a linear FN plot at low fields (or approximately=4*108 V m-1, (c) electron spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(43 citation statements)
references
References 31 publications
5
37
1
Order By: Relevance
“…It is found that the field emission characteristics of these micro-emitters are intrinsically changed by coating the emitters with a thin layer of dielectric material, this is in line with the results from previous investigations (AlQudah et al, 2015;Bajic et al, 1989;Latham & Mousa, 1986;Moran Meza et al, 2015;Mousa, 1987Mousa, , 1988Mousa, , 1992Mousa, , 1994Mousa, , 2007Mousa & Kelly, 2003;Mussa et al, 2012). By comparing the effects of different coating materials, we find the following effects.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It is found that the field emission characteristics of these micro-emitters are intrinsically changed by coating the emitters with a thin layer of dielectric material, this is in line with the results from previous investigations (AlQudah et al, 2015;Bajic et al, 1989;Latham & Mousa, 1986;Moran Meza et al, 2015;Mousa, 1987Mousa, , 1988Mousa, , 1992Mousa, , 1994Mousa, , 2007Mousa & Kelly, 2003;Mussa et al, 2012). By comparing the effects of different coating materials, we find the following effects.…”
Section: Discussionsupporting
confidence: 90%
“…Procedures for coating a tungsten (W) tip have been described elsewhere (Al-Qudah et al, 2015;Latham & Mousa, 1986;Madanat et al, 2015;Mousa et al, 2015). The micropoint emitters used were electrolytically etched from 0.1 mm diameter tungsten wires (99.95% purity), using a 2 M solution of NaOH and for carbon fiber tip were using a 0.1 M solution of sodium hydroxide solution .…”
Section: Methodsmentioning
confidence: 99%
“…This technology now makes it possible to prepare a cathode tip with a diameter of several nanometers. Composite micro-point cathodes have been prepared, with the aims of improving the emission characteristics needed for small bright electron sources, and reducing degradation of the electron emitter due to ion sputtering during emission (hence improving lifetime) (AlQudah et al, 2015;Latham & Mousa, 1986;Mousa, 1990;Mousa et al, 1994Mousa et al, , 2012Mousa & Al Share, 1999). The research reported here continues this work on composite micro-point cathodes.…”
Section: Introductionmentioning
confidence: 76%
“…The procedures used for coating tungsten emitters in the present work are the same as those described previously (AlQudah et al, 2015;Latham & Mousa, 1986). In all cases, the micro-point, nano-apex metallic emitters used were electrolytically etched from 0.1 mm diameter tungsten wires of 99.95% purity (Goodfellow Metals, England), using a 2 M solution of NaOH, and were then ultrasonically cleaned.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation